On the equiform geometry of special curves in hyperbolic and de Sitter planes - A. A. Abdel-Salam; M. I. Elashiry; M. Khalifa Saad (AIMS Mathematics, 2023)
In this paper, we aim to investigate the equiform differential geometric properties of the evolute and involute frontal curves in the hyperbolic and de Sitter planes. We inspect the relevance between evolute and involute frontal curves that relate to symmetry properties. Also, under the viewpoint of symmetry, we expand these notions to the frontal curves. Moreover, we look at the classification of these curves and introduce the notion of frontalisation for its singularities. Finally, we provide two numerical examples with drawing as an application, through which we authenticate our theoretical results.